DATA MINING FOR DETERMINING BOOK LOAN PATTERNS IN-LIBRARY USING APRIORI ALGORITHM - Preddy Marpaung (INFOKUM, 2019)
Data mining is the process of exploring the added value of knowledge so far not manually known from a data set using these techniques or methods. Data mining is a new science that has its roots in various fields of science such as artificial intelligence, machine learning, statistics, and databases. In the process of borrowing books, of course raw data will be processed by dividing it into different pieces of data. Among the lending data tables processed are general lending tables, 2-itemset candidate tables, lending tabular tables, support value tables, confidence value tables.